Peran Pengungkapan Emisi Karbon dalam Keputusan Investor di Pasar Berkembang: Sebuah Systematic Literature Review - Talita Adelia Zahira; Mukhtaruddin . (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to analyze the impact of carbon emission disclosure on investor decision-making in emerging markets using a Systematic Literature Review (SLR) method. Twenty-five selected articles from the ScienceDirect (Scopus) and Garuda (SINTA) databases were analyzed to examine disclosure characteristics and market response patterns. The findings indicate that the influence of carbon emission disclosure varies significantly depending on the substance of the information provided. Disclosures featuring concrete technical innovations—such as the utilization of industrial waste like copper slag for material efficiency—are responded to positively as adaptive business strategies that enhance firm value. Conversely, disclosures may trigger negative responses if perceived as a mere cost burden that reduces short-term profitability or constitutes a loss for stakeholders, particularly among retail investors. Institutional factors, including carbon tax regulations and external audits, were found to strengthen report credibility and mitigate greenwashing risks, which often lead to neutral market reactions. This study concludes that carbon transparency is not merely an administrative obligation but a strategic instrument to reduce information asymmetry and enhance competitiveness in emerging capital markets.